GUNS, POLITICS, AND CULTURE IN CENTRAL AFRICA - KALUSA, WALIMA T. (Journal of African history, 2018)
Using case studies, these sections tease out how exotic muzzleloaders interacted with nineteenth-century Central African sociocultural structures and politics.Through enlisting in colonial armed forces, the Ngoni, like the Yeke, found an opportunity to recreate their time-tested military traditions and ideas about honour.In rejecting technological determinism, Macola shows that the subjects of empire acted upon imported guns to undermine long-established kingdoms, to forge new polities, and to refashion their customsￂ -ￂ often in ways that gun manufacturers in Europe neither fathomed nor controlled.